Oxidative stress as the bridge between dyslipidemia and peritoneal ultrafiltration failure: A bi-center cross-sectional cohort study - Stepanova, N.; Korol, L.; Burdeyna, O.; Snisar, L.; Rysyev, A.; Filonov, V.; Poperechny, I. (Ukrainian Journal of Nephrology and Dialysis, 2023)
Oxidative stress and dyslipidemia are common concerns in patients undergoing peritoneal dialysis (PD) and are associated with adverse clinical outcomes. However, the interplay between these factors and their impact on peritoneal ultrafiltration (UF) remains poorly understood. Methods: In this bi-center cross-sectional cohort study, we examined the relationships between dyslipidemia, oxidative stress, and peritoneal UF in patients undergoing PD. A comprehensive set of oxidative stress markers, lipid profiles, and clinical variables were assessed. Results. Among the 114 patients, aged 55 (48-65) years, with a dialysis vintage of 31 (14-50) months, 76 (66.7%) were diagnosed with dyslipidemia. Patients with dyslipidemia experienced significantly higher proportions of patients with peritoneal UF below 400 mL per day, suggesting ultrafiltration failure (UFF) (χ2 = 4.9, p = 0.02). An elevated D/P creatinine ratio was associated with higher levels of total cholesterol (r = 0.39, p = 0.0005), low-density lipoprotein cholesterol (r = 0.26, p = 0.02), triglycerides (r = 0.33, p = 0.005), and the atherogenic index of plasma (AIP) (r = 0.27, p = 0.01). UF rate displayed a positive correlation with high-density lipoprotein cholesterol (r = 0.31, p = 0.003) and a negative correlation with AIP (r = -0.33, p = 0.004). The ROC analysis revealed that an AIP value exceeding 4.3 could effectively predict UFF, with a sensitivity of 83.3% and a specificity of 73.4% Dyslipidemia was significantly associated with increased intensity of oxidative stress, with elevated malondialdehyde (MDA) (p = 0.0002), oxidative stress index (OSI) (p < 0.0001), and reduced antioxidant markers. UFF was also associated with higher oxidative stress, as indicated by increased MDA (p = 0.005) and OSI (p = 0.0009). Patients with both dyslipidemia and UFF exhibited the highest levels of oxidative stress (p < 0.0001). Taking potential confounders into account in the ANCOVA analysis, a significant interaction effect of dyslipidemia (F = 7.6, p = 0.007) and UF rate (F = 8.6, p = 0.004) on oxidative stress was observed. Conclusion. Dyslipidemia and UFF are independently associated with elevated oxidative stress in PD patients, and their coexistence exacerbates this oxidative burden. Understanding these relationships is crucial for developing interventions to improve clinical outcomes in this population. Targeted therapies addressing oxidative stress and dyslipidemia warrant further investigation.